ANALISIS FAKTOR -FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA DI KABUPATEN DELI SERDANG - Tondang, Ifka Sri Ulina; Marbun, Gembira (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to determine and analyze the effect of Village Fund Management Apparatus Competence, Village Government Organizational Commitment, and Information Community Participation on Village Fund Management Accountability in Deli Serdang Regency. The type of research used in this research is quantitative research. Data collection was obtained by distributing questionnaires directly to respondents consisting of the Village Head, Village Secretary, Head of Government Section, Head of Service Section, Head of Welfare Section and Head of Financial Affairs/Treasury in villages in Deli Serdang. The location of the research was carried out at the village head office in villages in Deli Serdang Regency which had been randomly selected based on the simple random sampling method. Meanwhile, after calculating the sample using the Slovin formula, a sample of 57 respondents was obtained. The results in this study found that the competence of village fund management apparatus, village government organizational commitment, and community participation had a positive and significant influence on Village Fund Management Accountability in Deli Serdang Regency. And the result of the Adjusted R Square value is 0.846, which means (84.6%) of the independent variables are able to explain or describe the dependent variable, while the remaining 15.4% is explained or described by other variables not included in this research model. Keywords: Village Fund Management Apparatus Competence, Village Government Organizational Commitment, and Community Participation